Building an African Academic Law Journal: Some Reflections - Yongo, Cecil (Strathmore Law Review, 2018)
The Strathmore Law Review (SLR) enters its third volume this year. In this short non-academic essay, the author charts the path that the SLR has taken, discussing the underlying principles behind some of the important decisions made, as well as the lessons drawn from the first two years of publishing. The essay also broaches some of the critical issues in legal-academic writing today. Eventually, its insights aim at playing a role, however small, in helping decisionmakers create and facilitate better quality legal academic publications touching on African issues.